2018
DOI: 10.1002/chem.201704867
|View full text |Cite
|
Sign up to set email alerts
|

First Principles Calculation of the Reaction Rates for Ligand Binding to Myoglobin: The Cases of NO and CO

Abstract: Ligand binding by proteins is among the most fundamental processes in nature. Among these processes the binding of small gas molecules, such as O , CO and NO to heme proteins has traditionally received vivid interest, which was further boosted by their recently recognized significant role in gas sensing in the body. At the heart of the binding of these ligands to the heme group is the spinforbidden reaction between high-spin iron(II) and the ligand yielding a low-spin adduct. We use computational means to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 71 publications
(173 reference statements)
4
22
0
Order By: Relevance
“…Many theoretical studies have investigated atomic‐level spin‐inversion mechanisms in O 2 binding with a simplified model heme, namely, a Fe(II)‐porphyrin complex with a proximal imidazole or a related ligand . These theoretical studies have shown that the electronic ground state of the Fe(II)‐porphyrin complex with a d 6 configuration is a quintet spin state and that the second lowest spin state is a triplet state, although the energy difference between these spin states is very small .…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical studies have investigated atomic‐level spin‐inversion mechanisms in O 2 binding with a simplified model heme, namely, a Fe(II)‐porphyrin complex with a proximal imidazole or a related ligand . These theoretical studies have shown that the electronic ground state of the Fe(II)‐porphyrin complex with a d 6 configuration is a quintet spin state and that the second lowest spin state is a triplet state, although the energy difference between these spin states is very small .…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of experimental techniques (e.g., site-directed mutagenesis, EPR and Xe-binding X-ray diffraction) have been exploited to describe gas migration in the protein matrix [ 20 , 24 , 25 , 26 ]. Theoretical approaches, such as molecular dynamics (MD) simulations can provide complementary information on the dynamics of gas permeation through the protein matrix to obtain a full molecular-scale understanding of ligand transport [ 21 , 22 , 26 , 27 ]. First, we aimed at identifying those regions of the proteins that are most sensitive to gas ligand permeation.…”
Section: Resultsmentioning
confidence: 99%
“…We recently developed and validated against experimental results a three-state kinetic model for the study of ligand diffusion [ 22 ] that is much simpler than the complex Markov model used by Blumberger et al [ 30 , 31 , 32 ]. The model groups the instantaneous position of the ligands into three different categories: in the solvent phase, protein matrix or distal pocket ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations